A short review on Substantial role of Geopolymer in the sustainable construction industry. Issue 1 (1st January 2023) - Devarajan, Parthiban; Sivalinga vijayan, Dhanasingh; Sanjay Kumar, R; Arun Frait King, J
Abstract: Civil engineering has made significant strides in the discovery and application of novel materials during the past several decades. This list of notable substances contains a novel substance referred to as "Geopolymer, " which has been defined as a new bonding material derived from inorganic chemistry via polymerization of alumina-based silicate oxides with sodium, calcium, or potassium-based hydroxide compounds. The mixture of these chemical compounds, when applied, initiates an alkaline activation reaction that leads to the development of a nebulous structure. Unlike most organic or inorganic polymers, geopolymer is exemplified at temperatures below 1000°C. Because geopolymer is more eco-friendly than currently available construction adhesives, its use in building activities is on the rise. This review includes an examination of the history of geopolymer, the essential silicate material required to prepare geopolymer, the presence and reactions of the chemical compounds used to create alkaline activator solutions at different molar ratios, the curing conditions, the engineering characteristics of geopolymer activated specimens, and their resistance to chemicals. This review concludes that geopolymer technology is the best material for several applications in civil engineering in the twenty-first century.